Advertisement Remove all ads

Evaluate : (2a +3) (2a − 3) (4a2 + 9) - Mathematics

Sum

Evaluate : (2a +3) (2a − 3) (4a2 + 9)

Advertisement Remove all ads

Solution

(2a +3) (2a − 3) (4a2 + 9)

= [(2a)2 − (3)2] (4a2 + 9) ..........[(a+b) (a−b) = a2 − b2]

= (4a2 − 9) (4a2 + 9)

= (4a2)2 − (9)2 .........[(a+b) (a−b) = a2 − b2]

= 16a4 − 81

Concept: Product of Sum and Difference of Two Terms
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 12 Identities
Exercise 12 (A) | Q 5.05 | Page 150
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×